The Effects of a Learning Enhancement Program Integrated with Chatbot on Knowledge and Screening Practices for Cholangiocarcinoma among At-Risk Population - Sudsom, Ampai; Sudsom, Napadol (Nursing Journal of The Ministry of Public Health, 2025)
In areas with persistently high incidence rates of cholangiocarcinoma over many years, the development of an effective model for promoting knowledge and screening among at-risk groups is critically needed. This study aimed to investigate the effects of an educational program utilizing experiential learning cycle theory combined with chatbot technology on knowledge and screening practices for cholangiocarcinoma among at-risk populations. A quasi-experimental, single-group pre-test post-test design was employed with 31 purposively selected participants from the target at-risk population for cholangiocarcinoma screening. Participants engaged in an 8-week educational program incorporating experiential learning theory and chatbot technology. Data were collected using a questionnaire on knowledge and screening practices for cholangiocarcinoma, an observational checklist for screening practices, and a satisfaction assessment for the chatbot innovation. Data were analyzed using descriptive statistics and the Wilcoxon signed-ranks test. The results showed that after participating in the program, the mean scores of the sample group increased significantly in all aspects. The mean differences (MD) of the increases were as follows: 1) knowledge of liver fluke and cholangiocarcinoma: MD=1.65 (95% CI=1.09–2.20), 2) knowledge of cholangiocarcinoma screening: MD=3.32 (95% CI=2.66–3.99), 3) screening practice performance: MD=6.55 (95% CI=6.10–6.99), and 4) the chatbot innovation “Cholangiocarcinoma Awareness” received an overall user satisfaction rating at a high level. These findings reveal that the educational program utilizing experiential learning cycle theory in conjunction with chatbot technology can enhance knowledge and basic screening skills for cholangiocarcinoma among at-risk populations.